Does product market competition reduce inflation? Evidence from EU countries and sectors - Marcin Przybyla; Moreno Roma (European Central Bank (ECB), 2005)
In this paper we explore the link between the intensity of product market competition and inflation rates across EU countries and sectors. We consider long-term averages of inflation rates in order to remove the cyclical behavior of inflation over time and as alternative proxies of competition we use the level of mark-up, profit margin, the profit rate and a survey based “intensity of competition” variable. Results for both aggregate and sectoral panels show that the extent of product market competition, as proxied by the level of mark-up in particular, is an important driver of inflation. Notwithstanding some caveats associated with the measurement of the proxies of competition used, our findings suggest that higher product market competition reduces average inflation rates for a prolonged period of time. Moreover, results both at the aggregate and sectoral level are generally confirmed by a wide set of robustness tests.
Keywords: C21; C23; E31; 330; competition; Estimation and Panel Data Analysis; inflation; Wettbewerb; Mark-up Pricing; Preismanagement; Inflation; Schätzung; EU-Staaten